Sex Differences in Timeliness of Reperfusion in Young Patients With ST‐Segment–Elevation Myocardial Infarction by Initial Electrocardiographic Characteristics. Issue 6 (7th March 2018) - Gupta, Aakriti; Barrabes, Jose A.; Strait, Kelly; Bueno, Hector; Porta‐Sánchez, Andreu; Acosta‐Vélez, J. Gabriel; Lidón, Rosa‐Maria; Spatz, Erica; Geda, Mary; Dreyer, Rachel P.; Lorenze, Nancy; Lichtman, Judith; et al.
Abstract : Background: Young women with ST‐segment–elevation myocardial infarction experience reperfusion delays more frequently than men. Our aim was to determine the electrocardiographic correlates of delay in reperfusion in young patients with ST‐segment–elevation myocardial infarction. Methods and Results: We examined sex differences in initial electrocardiographic characteristics among 1359 patients with ST‐segment–elevation myocardial infarction in a prospective, observational, cohort study (2008–2012) of 3501 patients with acute myocardial infarction, 18 to 55 years of age, as part of the VIRGO (Variation in Recovery: Role of Gender on Outcomes of Young AMI Patients) study at 103 US and 24 Spanish hospitals enrolling in a 2:1 ratio for women/men. We created a multivariable logistic regression model to assess the relationship between reperfusion delay (door‐to‐balloon time >90 or >120 minutes for transfer or door‐to‐needle time >30 minutes) and electrocardiographic characteristics, adjusting for sex, sociodemographic characteristics, and clinical characteristics at presentation. In our study (834 women and 525 men), women were more likely to exceed reperfusion time guidelines than men (42.4% versus 31.5%; P <0.01). In multivariable analyses, female sex persisted as an important factor in exceeding reperfusion guidelines after adjusting for electrocardiographic characteristics (odds ratio, 1.57; 95% CI, 1.15–2.15). Positive voltage criteria for left ventricular hypertrophy and absence of a prehospital ECG were positive predictors of reperfusion delay; and ST elevation in lateral leads was an inverse predictor of reperfusion delay. Conclusions: Sex disparities in timeliness to reperfusion in young patients with ST‐segment–elevation myocardial infarction persisted, despite adjusting for initial electrocardiographic characteristics. Left ventricular hypertrophy by voltage criteria and absence of prehospital ECG are strongly positively correlated and ST elevation in lateral leads is negatively correlated with reperfusion delay.